Investigation of exchange coupled bilayer Fe/CuMnAs by pump-probe experiment - Saidl, V.; Němec, P.; Wadley, P.; Edmonds, K.W.; Campion, R.P.; Novák, V.; Gallagher, B.L.; Trojánek, F. (Wiley, 2017)
Time-resolved pump-probe magneto-optical method was used to study Fe/CuMnAs bilayer. The probe polarization dependence was used to identify and separate parts of detected signals due to Faraday and Voigt magneto-optical effects that provide information about pump-induced magnetization precession in ferromagnetic (FM) Fe and demagnetization in antiferromagnetic (AF) CuMnAs layers, respectively. We observed a 180 deg phase shift in the precession signal at non-zero magnetic field that we interpreted as a signature of the magnetic anisotropy induced in the FM by the adjacent AF layer. Unlike in x-ray magnetic linear dichroism experiments, we did not observe any significant reorientation of magnetic moments in CuMnAs by external magnetic field due to the interlayer exchange coupling with Fe. Differences between these two experimental techniques, providing the distinct pictures, are discussed.